Compositional Peculiarities of Mamin-Sibiriak's Novel "The Privalov Millions" - Galinienė, Liudmila (Literatūra, 1967)
The aim of the article is to investigate the composition of the novel as an expressive means to render its idea content. The here discussed novel – "The Privalov Millions" is the first book of Mamin-Sibiriak's "Urals" series. Its idea content is many-sided and has many branches. Whereas in his "Autobiographic Note" the author points out that the main thing in his novel is the destiny of Sergej Privalov and his complicated evolution.As theoretical basis for the analysis of so complicated a work was used the view of K. Fedin, a Soviet writer, that composition is not the self-will of an author but the logic dictated by the development of the theme. Therefore the author of the article endeavours to prove that the composition of "The Privalov Millions" expresses the essence of the novel's idea content.The most typical peculiarity of the novel's composition is the writer's desire to group all the acting personages, events, all the material of the novel round the chief personage – Sergej Privalov.Thereby in separate parts of the work we find a gradual accumulation of material that characterises surrounding reality and has a significance of its own. And so in the course of the action the novel's centre of gravity shifts from the chief personage to his surroundings. The surroundings stop being a mere background revealing the portrait of Privalov. Now it is the reverse: Privalov's picture, his personality serve to unite the separate parts of the novel, its components. The composition of "The Privalov Millions" expresses all the idea content of the novel and clearly surpasses the author's conception.
Keywords: -